The Impact of Early Weaning on Nutritional Status of Children Aged 6–24 Months in Cinambo - Maidartati, Maidartati; Iklima, Nurul; Irawan, Erna; Sari, Putri Puspita; Wijayanti, Anita Putri (SAFE-Network, 2025)
The weaning period is critical as it marks the transition from breastfeeding to solid foods, during which infants are particularly susceptible to nutritional disorders. The optimal weaning age is generally around two years, as breastfeeding until this age significantly supports a child's growth. Factors influencing weaning include parental education, economic status, parental employment, and the age of weaning. The timing of weaning is related to nutritional status since a child's diet shifts from exclusively breast milk to a combination of breast milk and solid foods, with increased energy and nutritional needs. This study investigates the relationship between weaning age and nutritional status in children aged 6-24 months at Puskesmas Cinambo, Bandung City. Employing a cross-sectional analytical design, the population includes mothers of children in this age range, totaling 534 respondents. Accidental sampling yielded 118 respondents over one week. Data were collected through questionnaires and analyzed using univariate and bivariate methods, with significance set at p<0.05. Results indicated that 52.5% of respondents had normal nutritional status, while 47.5% were undernourished. Most weaning ages were found to be inappropriate, with 66.1% weaning before the recommended age of 24 months. The Spearman Rank test revealed a significant relationship (p=0.020), confirming H1. In conclusion, there is a relationship between weaning age and nutritional status in children aged 6-24 months at Puskesmas Cinambo. Health services should provide regular education on appropriate weaning practices to enhance the nutritional status of this age group.